2021
DOI: 10.1101/2021.02.02.21251020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severe Covid-19 Is Marked by Dysregulated Serum Levels of Carboxypeptidase A3 and Serotonin

Abstract: The immune response plays a critical role in the pathophysiology of SARS-CoV-2 infection ranging from protection to tissue damage. This is observed in the development of acute respiratory distress syndrome when elevated levels of inflammatory cytokines are detected. Several cells of the immune response are implied in this dysregulated immune response including innate immune cells and T and B cell lymphocytes. Mast cells are abundant resident cells of the respiratory tract, able to rapidly release different inf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…As stated earlier, 5-HT cannot cross the BBB and the central 5-HT is synthesized in the brainstem only from the absorbed tryptophan, which reaches the brainstem by crossing the BBB as free tryptophan [42], given the fact that tryptophan circulates as bound tryptophan (loosely bound to albumin) which dissociates from the albumin near the BBB. Interestingly, the 5-HT deficiency state in COVID-19, as suggested above, has been vindicated in a recent study [43], where it has been found that the 5-HT levels in coronavirus patients are indeed reduced though the researchers assumed [43] that the reduction of 5-HT may be due to the alteration in enterochromaffin cell functions or increased 5-HT degradation by monoamine oxidase (MAO, a family of enzymes where MAO-A is specifically involved in the process of breaking down of 5-HT to 5-hydroxyindoleacetic acid, 5-HIAA). In another study [44], an apparent increase in plasma 5-HT level in a specific case has been attributed to the possibility of delayed or insufficient breakdown of 5-HT to 5-HIAA in the liver, although, in such case, the brain 5-HT level (central 5-HT) should remain unaffected as 5-HT cannot cross the BBB.…”
Section: Second Does Anosmia Then Results From Coronavirus Induced Damage Of the Olfactory Neurons?mentioning
confidence: 71%
“…As stated earlier, 5-HT cannot cross the BBB and the central 5-HT is synthesized in the brainstem only from the absorbed tryptophan, which reaches the brainstem by crossing the BBB as free tryptophan [42], given the fact that tryptophan circulates as bound tryptophan (loosely bound to albumin) which dissociates from the albumin near the BBB. Interestingly, the 5-HT deficiency state in COVID-19, as suggested above, has been vindicated in a recent study [43], where it has been found that the 5-HT levels in coronavirus patients are indeed reduced though the researchers assumed [43] that the reduction of 5-HT may be due to the alteration in enterochromaffin cell functions or increased 5-HT degradation by monoamine oxidase (MAO, a family of enzymes where MAO-A is specifically involved in the process of breaking down of 5-HT to 5-hydroxyindoleacetic acid, 5-HIAA). In another study [44], an apparent increase in plasma 5-HT level in a specific case has been attributed to the possibility of delayed or insufficient breakdown of 5-HT to 5-HIAA in the liver, although, in such case, the brain 5-HT level (central 5-HT) should remain unaffected as 5-HT cannot cross the BBB.…”
Section: Second Does Anosmia Then Results From Coronavirus Induced Damage Of the Olfactory Neurons?mentioning
confidence: 71%
“…It has been postulated that SARS-CoV-2 might have an indirect effect on enteroendocrine cells (EEC), triggering the release of neuroactive agents such as the emesis inducing serotonin [14]. Most studies showed that patients with COVID-19 have higher plasma serotonin levels and this correlates with increased IL-6 [15,16], while others concluded they have decreased serotonin levels [17]. Considering serotonin's role in regulating innate and adaptive immune responses [18], the observed beneficial effect of ondansetron might be due to the modulation of serotonin levels or could also be linked with a direct effect on the immune system [19] or on known COVID-19 comorbidities, such liver and kidney disease or complications, such as thrombosis [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies have revealed an elevated density of perivascular and septal MCs in the post-mortem lung biopsies from COVID-19 patients (77) and higher number of activated MCs in the bronchoalveolar lavage fluid of COVID-19 patients as compared to samples from healthy individuals (78). Furthermore, there was more MC-specific protease, CPA3 found in the serum of COVID-19 patients comparing to control group and there was a significant positive correlation between CPA3 and circulating neutrophils as well as C-reactive protein which are associated with Accepted Article exacerbated inflammatory response and thereby disease severity in COVID-19 patients (70).…”
Section: Role Of Mcs In Coronavirus Infectionmentioning
confidence: 92%
“…Coronaviruses are single positive-strand, enveloped ribonucleic acid (70) viruses (71,72). Within the last 20 years, there have been three highly pathogenic, zoonotic diseases caused by coronaviruses, with Severe Acute Respiratory Syndrome (SARS-CoV-1) first being detected in China in 2002 and then Middle East Respiratory Syndrome coronavirus (MERS-CoV) in Saudi Arabia in 2012, both caused outbreaks and spread globally (71,73,74).…”
Section: Role Of Mcs In Coronavirus Infectionmentioning
confidence: 99%